Meta-analysis of randomized controlled trials assessing the efficacy of nigella sativa supplementation for allergic rhinitis treatment - He, Yuxiao; Hu, Xiaoyan; Chang, Lanyin; Liu, Shuang; Lv, Liangge; Qin, Gang; Jiang, Liang (Frontiers in Pharmacology, 2024)
Background: Demonstrating the positive effects of Nigella sativa supplementation (Nigella spp) on Allergic Rhinitis (AR) treatment is challenging. To investigate the role of Nigella spp in managing AR, a comprehensive review through systematic reviews and meta-analyses was conducted. Purpose: To carry out a meta-analysis of clinical trials that used Nigella spp in treating AR based on current data. Study Design: A meta-analysis of randomized controlled trials (RCTs) was performed. Methods: Various databases, including PubMed, Web of Science, Embase, Science Direct, Springer Link and the Cochrane Library, were searched until October 2023 to obtain RCTs assessing impact of Nigella spp in the control of AR. The current meta-analysis was carried out with a random-effects model. Results: There were 8 studies enrolled, and our meta-analysis findings revealed that, relative to the control group, observation group exhibited the markedly increased total effective rate for allergic rhinitis treatment (odds ratio [OR] = 4.24, 95% confidence interval [CI] (2.57, 7.27), and P < 0.00001); three studies showed that the effect of Nigella spp for nasal symptoms treatment among patients with allergic rhinitis was superior in observation group to control group [mean difference = -2.60, 95% CI ( -2.82, -2.38), P < 0.00001]; adverse effects occurred in five studies, all of which were transient, did not require medical intervention, and were not statistically significant between the two groups [OR = 1.01, 95% CI (0.59, 1.73), P = 0.98]. Conclusion: The observation group demonstrated relative safety and had an enhanced effect on allergic rhinitis treatment and total nasal symptom improvement than the control group. The inclusion of fewer studies and the lower quality of trial design might affect the stability of the results. However, the evidence-based findings that Nigella spp for allergic rhinitis treatment is more accurate should be validated in future large-scale, multicenter, and well-designed RCTs.